Flower‐like Ni(II)‐based Metal‐organic Framework‐decorated Ag Nanoparticles: Fabrication, Characterization and Electrochemical Detection of Glucose. Issue 11 (11th July 2019) - Peng, Xuerong; Wan, Yue; Wang, Yanying; Liu, Tao; Zou, Ping; Wang, Xianxiang; Zhao, Qingbiao; Ding, Fang; Rao, Hanbing
Abstract: Glucose concentration monitoring is important for the prevention, diagnosis and treatment of diabetes. In this work, a composite material of AgNPs/MOF‐74(Ni) was prepared for electrochemical determination of glucose. AgNPs/MOF‐74(Ni) was characterized by X‐ray diffraction (XRD), scanning electron microscopy (SEM), transmission electron microscopy (TEM) and X‐ray photoelectron spectroscopy (XPS). The electrochemical properties of the glassy carbon electrodes modified with the AgNPs/MOF‐74(Ni) composites were characterized by cyclic voltammetry (CV) and current‐time curve (I‐t curve) with three electrode system. The determination of glucose with the electrode modified by AgNPs/MOF‐74(Ni) has a linear range of 0.01∼4 mM with the correlation coefficient (R 2 ) of 0.994. The detection limit is 4.7 μM (S/N=3) and the sensitivity is 1.29 mA ⋅ mM −1  ⋅ cm −2 . In addition, this sensing system possesses reasonable reproducibility and stability. The good performance of electrochemical determination for glucose is attributed to the concerted effect of silver nanoparticles and MOF‐74(Ni) on the promotion of glucose oxidation Abstract :